2022
DOI: 10.1590/s1677-5538.ibju.2022.99.07
|View full text |Cite
|
Sign up to set email alerts
|

Epididymal disjunction anomalies in undescended testis – a factor associated with spermatic obstruction

Abstract: Background:To analyze the incidence of epididymal anomalies (EAs) associated to spermatic obstruction in patients with undescended testis (UT) according to testicular position and age. Materials and Methods: We studied 87 patients (110 testis) with cryptorchidism and analyzed the presence of EAs correlated with the testicular position, age and patency of the processus vaginalis (PV). To analyze the relations between the testis and epididymis we considered three situations: (a) Normal pattern: the epididymis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…In man, efferent ducts form the bulk of what is called the head or proximal part of the epididymis (Sullivan et al 2019; Légaré and Sullivan 2020) and pathological changes are more commonly found in this region in larger mammals, including obstructive lesions, which contribute substantially to male infertility (Ball and Mitchinson 1984;McEntee 1990;Rajalakshmi et al 1990; Pal et al 2006). The high incidence of epididymal disjunctions associated with epididymal anomalies points to the importance of understanding the endocrine regulation for development of the male ductal systems (Logsdon et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In man, efferent ducts form the bulk of what is called the head or proximal part of the epididymis (Sullivan et al 2019; Légaré and Sullivan 2020) and pathological changes are more commonly found in this region in larger mammals, including obstructive lesions, which contribute substantially to male infertility (Ball and Mitchinson 1984;McEntee 1990;Rajalakshmi et al 1990; Pal et al 2006). The high incidence of epididymal disjunctions associated with epididymal anomalies points to the importance of understanding the endocrine regulation for development of the male ductal systems (Logsdon et al 2022).…”
Section: Introductionmentioning
confidence: 99%